Identification of recurrent USP48 and BRAF mutations in Cushing’s disease - Chen, Jianhua; Jian, Xuemin; Deng, Siyu; Ma, Zengyi; Shou, Xuefei; Shen, Yue; Zhang, Qilin; Song, Zhijian; Li, Zhiqiang; Peng, Hong; Peng, Cheng; Chen, Min; et al. (Nature communications, 2018)
Cushing’s disease results from corticotroph adenomas of the pituitary that hypersecrete adrenocorticotropin (ACTH), leading to excess glucocorticoid and hypercortisolism. Mutations of the deubiquitinase gene USP8 occur in 35–62% of corticotroph adenomas. However, the major driver mutations in USP8 wild-type tumors remain elusive. Here, we report recurrent mutations in the deubiquitinase gene USP48 (predominantly encoding p.M415I or p.M415V; 21/91 subjects) and BRAF (encoding p.V600E; 15/91 subjects) in corticotroph adenomas with wild-type USP8 . Similar to USP8 mutants, both USP48 and BRAF mutants enhance the promoter activity and transcription of the gene encoding proopiomelanocortin (POMC), which is the precursor of ACTH, providing a potential mechanism for ACTH overproduction in corticotroph adenomas. Moreover, primary corticotroph tumor cells harboring BRAF V600E are sensitive to the BRAF inhibitor vemurafenib. Our study thus contributes to the understanding of the molecular mechanism of the pathogenesis of corticotroph adenoma and informs therapeutic targets for this disease. In this study the authors report USP48 and BRAF are frequently mutated in USP8 wild-type corticotroph adenomas, and cause Cushing’s disease mainly through promoting the promoter activity of POMC. Inhibition of BRAF may be a promising therapeutic strategy for the treatment of patients with BRAF-mutated corticotroph adenomas.